2017
DOI: 10.17221/88/2016-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genetic diversity of selected Fagus sylvatica L. populations in the Czech Republic using nuclear microsatellites

Abstract: Cvrčková H., Máchová P., Poláková L., Trčková O. (2017): Evaluation of the genetic diversity of selected Fagus sylvatica L. populations in the Czech Republic using nuclear microsatellites. J. For. Sci., 63: 53-61.Fagus sylvatica Linnaeus (European beech), the ecologically and economically most important broadleaved tree species in the Czech Republic, was strongly reduced in the past. Today there are efforts to increase the proportion of beech to ensure optimal forest tree species composition. When extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Across the studied populations, the highest number of private alleles was found on locus Fagsyl_003093, followed by loci Fagsyl_003849, mfc5 and csolfagus_29. Cvrčková et al (2017) observed the highest number of private alleles in a population which was geographically very close to population 9 in our study and which also exhibited the highest number of private alleles. This may indicate a bigger genetic differentiation of beech individuals in this region which is also shown in the PCoA analysis (Figure 2).…”
Section: Intra and Interpopulation Genetic Diversitysupporting
confidence: 63%
See 1 more Smart Citation
“…Across the studied populations, the highest number of private alleles was found on locus Fagsyl_003093, followed by loci Fagsyl_003849, mfc5 and csolfagus_29. Cvrčková et al (2017) observed the highest number of private alleles in a population which was geographically very close to population 9 in our study and which also exhibited the highest number of private alleles. This may indicate a bigger genetic differentiation of beech individuals in this region which is also shown in the PCoA analysis (Figure 2).…”
Section: Intra and Interpopulation Genetic Diversitysupporting
confidence: 63%
“…(Nei, 1972(Nei, , 1987 H e = 0.695 on 16 loci. A similar study in the Czech Republic was carried out by Cvrčková et al (2017). They evaluated 390 beech individuals from 13 populations on 12 SSR markers where seven loci were identical with the ones we used in our study.…”
Section: Intra and Interpopulation Genetic Diversitymentioning
confidence: 98%